‘Inappropriate’ attenders to the Adult Emergency Department – A Critical Review - Lloyd-Jones, Angharad (2012)
Background: The Department of Health (DoH) emphasise the increased attendance rates to the Emergency Department (ED) over the last decade from 14,044,018 in 2001- 2 (DoH, 2002) up to 21,342,543 in 2010-11 (DoH, 2010-11). Ainsworth (2008) identified that annually up to 14 million attenders could have been treated by their General Practitioner which coincides with Lee, Hazlett, Chow, Lau, Kam, Wong & Wong’s (2003) suggestion that ‘inappropriate’ attenders are the cause of the increased attendance rates. The literature is heavily criticised for the lack of definition and this is respective in society illustrated through the increased attendance rates. Aims: This study aims to critically review literature on ‘inappropriate’ adult attenders to the Emergency Department. Method: A critical review was used, reviewing 24 literature articles from ScienceDirect, CINAHL, Medline and Embase using the keywords: “Emergency Service, Hospital/”, “Emergency Medical Services/”, “Emergency Department.mp”, “Inappropriate.mp”, “Primary Care.mp or Primary Health Care/”. Findings: A lack of consistency between definitions of ‘inappropriateness’ to the ED was found from the literature, leading to a vast discrepancy between definitions generated by healthcare professional’s opinions and patients’. The role of the ED was found to relate to functionality through name, suggesting that society is unaware of the role of the ED. The reasons patients attend ED are variable, complex and consider health seeking behaviour from a psychology approach. VIII Conclusion: The review found that the definition of ‘inappropriate attendance’ is elusive and therefore open for interpretation by staff and patients. The use of personal opinions as a definition has created a vast discrepancy between staff and patients’, leading to ‘blame’ and ‘labelling’ of patients.